How and why a multifaceted intervention to improve adherence post-MI worked for some (and could work better for others): an outcome-driven qualitative process evaluation - Holly O Witteman; Laura Desveaux; Justin Presseau; Noah Michael Ivers; Marianne Saragosa; Kirstie Russell; Nicola McCleary; J-D Schwalm (BMJ Open)
Objectives To explore (1) the extent to which a multicomponent intervention addressed determinants of the desired behaviours (ie, adherence to cardiac rehabilitation (CR) and cardiovascular medications), (2) the associated mechanism(s) of action and (3) how future interventions might be better designed to meet the needs of this patient population.Design A qualitative evaluation embedded within a multicentre randomised trial, involving purposive semistructured interviews.Setting Nine cardiac centres in Ontario, Canada.Participants Potential participants were stratified according to the trial’s primary outcomes of engagement and adherence, resulting in three groups: (1) engaged, adherence outcome positive, (2) engaged, adherence outcome negative and (3) did not engage, adherence outcome negative. Participants who did not engage but had positive adherence outcomes were excluded. Individual domains of the Theoretical Domains Framework were applied as deductive codes and findings were analysed using a framework approach.Results Thirty-one participants were interviewed. Participants who were engaged with positive adherence outcomes attributed their success to the intervention’s ability to activate determinants including behavioural regulation and knowledge, which encouraged an increase in self-monitoring behaviour and awareness of available supports, as well as reinforcement and social influences. The behaviour of those with negative adherence outcomes was driven by beliefs about consequences, emotions and identity. As currently designed, the intervention failed to target these determinants for this subset of participants, resulting in partial engagement and poor adherence outcomes.Conclusion The intervention facilitated CR adherence through reinforcement, behavioural regulation, the provision of knowledge and social influence. To reach a broader and more diverse population, future iterations of the intervention should target aberrant beliefs about consequences, memory and decision-making and emotion.Trial registration number ClinicalTrials.gov registry; NCT02382731